The competition of scientific and technical literature translators as the way of translation competence formation of students studying at electrical engineering department of Samara State Technical University is considered - Amalia L. Kyuregyan; Olga A. Rybalchik (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Distribution of scientific and technical knowledge demands both development of the theory of translation business, and improvement of professional translators training. In this paper the Competition of scientific and technical literature translators as the way of translation competence formation of students studying at Electrical Engineering department of Samara State Technical University is considered. The translation competence means the concept characterizing professional ability of a translator to carry out communicative mediation in various fields of activity, namely the set of knowledge, skills directed to adequate perception, text interpretation and communicative effect. Also typical mistakes made by students while translating the text and recommendations to avoid them are given, as the translation of technical texts is a hard process in which a lot of parameters and features of both native and foreign languages have to be considered.